Gender differences in pole vault approach run kinematics and step parameter asymmetry during an elite indoor competition. (4th July 2021) - Panoutsakopoulos, Vassilios; Theodorou, Apostolos S.; Kotzamanidou, Mariana C.; Exell, Timothy A.; Kollias, Iraklis A.
ABSTRACT: The purpose of the study was to examine gender differences of approach run kinematics and step parameters asymmetry. The attempts of 24 pole vaulters (11 males, 13 females) during a major indoor competition were examined. Step length, frequency and average velocity of the last eight steps were calculated using spatiotemporal data acquired with panning video recordings (300 fps) of the participants' best attempt. The asymmetry of the step parameters was quantified using the symmetry angle method. Results indicated significant (p < .05) gender differences in step length and average step velocity, as well as inter-limb asymmetry for step length and frequency. In addition, a significant (p < .05) pole carrying side effect in average step velocity was revealed. Significant (p < .05) asymmetry for step length was observed in 2 male and 5 female vaulters. No significant (p > .05) asymmetry for step frequency and average velocity were observed in women. In conclusion, gender differences seem to be attributed to the pole properties and the physical conditioning of the pole vaulters, since the pole carrying at the final stage of the approach run requires large power/explosive strength capabilities.